Sustainability Accounting Disclosure, Firm Value, and Intellectual Capital Mechanism - Werastuti, Desak Nyoman Sri; Atmadja, Anantawikrama Tungga; Adiputra, I Made Pradana; Nugraha, Kadek Mitananda Pradnya (AKRUAL: Jurnal Akuntansi, 2025)
Research Background: Sustainability accounting disclosures include voluntary disclosures aimed at creating a positive perception among stakeholders. Introduction / Objectives: This study aims to determine the impact of sustainability accounting disclosure on firm value through intellectual capital. Methods: The methods used were OLS regression and bootstrapping. The study sample consisted of 34 of the strongest banks from The ASEAN Banker for the period 2018 to 2024. Results: The study found that sustainability accounting disclosure has a direct effect on firm value without going through intellectual capital. However, intellectual capital does not act as a mediator in the effect of sustainability disclosure on firm value. Sustainability accounting disclosure can influence investment decisions. Signaling theory remains relevant in explaining the role of disclosure in investor investment decisions. Intellectual capital is more important for strengthening the breadth of sustainability accounting disclosure than for intermediating information to investors. Conclusion: These results validate the relevance of signaling theory, which states that sustainability disclosure is a strategic tool for banks to demonstrate their commitment to sustainability principles. The Asian Banker believes it is important to consider sustainability disclosure as part of its assessment metrics. This will encourage banks to further enhance transparency, competitiveness, and investor trust. Furthermore, banks can demonstrate their commitment to maintaining sustainability and sound risk management.